Protein Kinases of the Hippo Pathway: Regulation and Substrates - Avruch, Joseph (2012)
The “Hippo” signaling pathway has emerged as a major regulator of cell proliferation and survival in metazoans. The pathway, as delineated by genetic and biochemical studies in Drosophila, consists of a kinase cascade regulated by cell-cell contact and cell polarity that inhibits the transcriptional coactivator Yorkie and its proliferative, anti-differentiation, antiapoptotic transcriptional program. The core pathway components are the GC kinase Hippo, which phosphorylates the noncatalytic polypeptide Mats/Mob1 and, with the assistance of the scaffold protein Salvador, phosphorylates the ndr-family kinase Lats. In turn phospho-Lats, after binding to phospho-Mats, autoactivates and phosphorylates Yorkie, resulting in its nuclear exit. Hippo also uses the scaffold protein Furry and a different Mob protein to control another ndr-like kinase, the morphogenetic regulator Tricornered. Architecturally homologous kinase cascades consisting of a GC kinase, a Mob protein, a scaffolding polypeptide and an ndr-like kinase are well described in yeast; in S. cerevisiae e.g., the MEN pathway promotes mitotic exit whereas the RAM network, using a different GC kinase, Mob protein, scaffold and ndr-like kinase, regulates cell polarity and morphogenesis. In mammals, the Hippo orthologues Mst1 and Mst2 utilize the Salvador ortholog WW45/Sav1 and other scaffolds to regulate the kinases Lats1/Lats2 and ndr1/ndr2. As in Drosophila, murine Mst1/Mst2, in a redundant manner, negatively regulate the Yorkie ortholog YAP in the epithelial cells of the liver and gut; loss of both Mst1 and Mst2 results in hyperproliferation and tumorigenesis that can be largely negated by reduction or elimination of YAP. Despite this conservation, considerable diversification in pathway composition and regulation is already evident; in skin e.g., YAP phosphorylation is independent of Mst1Mst2 and Lats1Lats2. Moreover, in lymphoid cells, Mst1/Mst2, under the control of the Rap1 GTPase and independent of YAP, promotes integrin clustering, actin remodeling and motility while restraining the proliferation of naïve T cells. This review will summarize current knowledge of the structure and regulation of the kinases Hippo/Mst1&2, their noncatalytic binding partners, Salvador and the Rassf polypeptides, and their major substrates Warts/Lats1&2, Trc/ndr1&2, Mats/Mob1 and FOXO.